Civil Forfeiture as a Legal Mechanism for Recovery of State Losses in Corruption Cases in Indonesia - Malik, Faissal; Amriyanto; Syafari, Tri (Fakultas Syariah INSURI Ponorogo, 2026)
The recovery of state financial losses from corruption remains a central challenge in Indonesia's anti-corruption framework. Despite the availability of various recovery mechanisms, questions persist regarding their effectiveness and conformity wth the principle of proportionality and national legal policy. This study examines the application of proportionality in state loss recovery policies and formulates a future-oriented legal policy to enhance recovery effectiveness. Employing a normative legal research method, this study applies Robert Alexy's proportionality test, suitability, necessity, and proportionality in the strict sense to assess criminal restitution, post-conviction asset confiscation, and administrative and civil forfeiture mechanisms. The findings reveal that Indonesia's current recovery framework is fragmented and predominantly reliant on repressive, criminal-based approaches, resulting in limited asset recovery. The novelty of this study lies in its proportionality-based formulation of civil forfeiture as an integrated administrative recovery model that prevents asset dissipation while safeguarding due process and property rights. This study argues that proportionality does not weaken anti-corruption efforts, but rather provides a normative foundation for designing recovery policies that are effective, balanced, and capable of delivering measurable public benefits.